2012
DOI: 10.1186/1475-2875-11-251
|View full text |Cite
|
Sign up to set email alerts
|

The detection of pfcrt and pfmdr1 point mutations as molecular markers of chloroquine drug resistance, Pahang, Malaysia

Abstract: BackgroundMalaria is still a public health problem in Malaysia with chloroquine (CQ) being the first-line drug in the treatment policy of uncomplicated malaria. There is a scarcity in information about the magnitude of Plasmodium falciparum CQ resistance. This study aims to investigate the presence of single point mutations in the P. falciparum chloroquine-resistance transporter gene (pfcrt) at codons 76, 271, 326, 356 and 371 and in P. falciparum multi-drug resistance-1 gene (pfmdr1) at codons 86 and 1246, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 41 publications
8
35
2
Order By: Relevance
“…These findings corroborate well with the previous findings [12], [17], [19], [32]. In the present study, all the CQ resistant isolates showed mutational change at position 86Y confirming the role of this mutation in the CQ resistance.…”
Section: Discussionsupporting
confidence: 93%
“…These findings corroborate well with the previous findings [12], [17], [19], [32]. In the present study, all the CQ resistant isolates showed mutational change at position 86Y confirming the role of this mutation in the CQ resistance.…”
Section: Discussionsupporting
confidence: 93%
“…Similar findings have been reported from Malaysia and Iran (Rastaghi et al, 2008;Atroosh et al, 2012). No significant difference in the prevalence of pfcrt and pfmdr1 mutations between subclinical and clinical infection of malaria parasites was noted in this survey.…”
Section: Discussionsupporting
confidence: 92%
“…falciparum CQ, PYR and SDX resistant previously reported in Pahang [9], Lundu, Sarawak [8] and Sabah: Kalabakan (Tawau Division) [6, 30], Keningau & Nabawan (Interior Division) [39], Kota Kinabalu (West Coast Division) [35], a Kota Marudu—present study, b Kudat [35] (Kudat Division). This map was generated by using SimpleMappr online software [40].…”
Section: Discussionmentioning
confidence: 50%
“…A hundred percent prevalence of K76T mutation was reported in Lundu, Sarawak in a study conducted in 1999 and 2000 (Fig 1 and Table 3) [8]. A previous study by Atroosh et al[9] have reported high prevalence rate of pfcrt K76T mutation in P . falciparum isolates in the Peninsular Malaysia (West Malaysia) area such as Pahang (Fig 1 and Table 3).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation